Dinamika Konflik, Komitmen, dan Kepemimpinan dalam Komunitas HOMPIMPA Semarang - Sari Pujiastuti, Natalia; Anandasari, Fajar Rizki; Nimas Ayu, Syabilla; Farida, Sinta; Meilisa, Nur Sukma; Adit Prasetya, Ariel (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study examined the internal dynamics of the Hompimpa Semarang Community, a youth-based cultural group dedicated to preserving traditional games within an increasingly digital society. The research aimed to understand why the community experienced declining member participation, recurring interpersonal tensions, and weakening organizational structure after its reactivation following the pandemic. The study explored how these issues affected the community’s ability to sustain its cultural and educational programs. The research employed a literature-based qualitative method to analyze organizational conflict, member commitment, and leadership practices within the community. Data were reviewed through documented activities, internal narratives, and theoretical frameworks related to conflict management, collective engagement, and transformational leadership.The findings indicated that conflicts were primarily triggered by unequal task distribution, communication gaps between divisions, and limited face-to-face interaction caused by differing academic schedules. These factors contributed to reduced motivation and weakened group cohesion. However, the study found that participatory and reflective leadership successfully transformed tensions into opportunities for collective learning, leading to increased trust and renewed commitment among members. Structural limitations, particularly the absence of formal recognition from academic institutions, continued to hinder long-term stability. The study offered original insights into how informal youth communities could strengthen sustainability by developing clear organizational structures, formal legitimacy, and consistent transformational leadership. It also highlighted the importance of communication systems and recognition mechanisms in rebuilding collective responsibility. These findings may inform future studies on youth-based cultural organizations and community-led cultural preservation efforts.